Transcatheter arterial embolization for gastroduodenal ulcers bleeding - Širvinskas, Audrius; Smolskas, Edgaras; Mikelis, Kipras; Brimas, Gintautas (Lietuvos chirurgija, 2016)
Background and objectiveTranscatheter arterial embolization is an alternative to surgical management when dealing with recurrent bleeding from a peptic ulcer after a failed endoscopic treatment. The purpose of this study is to analize the ffectiveness and outcomes of transcatheter arterial embolization and identify the factors that influenced morbidity and mortality rates.Materials and methodsA retrospective single-center analysis was performed of 20 patients who underwent transcatheter arterial embolization for acute upper astrointestinal bleeding from gastroduodenal ulcers from 2012 to 2015 at the Republic Vilnius University Hospital. We analyzed the association of early rebleeding and mortality with sex, age, number of units of blood components administered to the patients, length of hospital stay, time passed until embolization, therapeutic or prophylactic embolization.ResultsThe embolization procedure had a technical success rate of a 100%. 14 (70%) were prophylactic embolizations and 6 (30%) were therapeutic embolizations. Three patients (15%) had an episode of rebleeding following embolization, 5 (25%) patients died. Patients that died received statistically significant larger number of blood components (p=0.04 for frozen plasma;p=0.01 for packed red blood cells) and patients that survived had a shorter hospital stay (p=0.05). No associations were observed between rebleeding and factors analyzed.ConclusionsTranscatheter arterial embolization is a feasible method for the treatment of rebleeding in gastroduodenal ulcer after endoscopic treatment, resulting in high rates of technical and clinical success and low complication rates. Further prospective randomized trials are needed to obtain more evidence.
Keywords: peptic ulcer; hemorrhage; transcatheter arterial embolization